Automated power supply control system for a food industry enterprise using a photovoltaic plant and energy storage - Baliuta, Serhii; Zinkevych, Petro (My University, 2022)
Introduction. Studies were carried out on the power supply control process of a food industry enterprise using a photoelectric plant and electric energy storage to ensure the efficiency of transmission and use of electrical energy. Materials and methods. The studies were carried out using the methods of modern theory of automatic control and system analysis of control processes. Results and discussion. The main stages of the power supply control process using a photovoltaic plant and an energy storage system are defined: basic control functions – registration of electric energy consumption, forecasting of electric energy generation using a photovoltaic plant, forecasting of electric energy consumption, determination of parameters of the electric energy storage system, analysis power supply system modes; conditions for providing control functions – information on solar radiation; data on electric energy generation using photovoltaic plant, data on electric energy consumption, limitations and tariffs for electric energy, requirements for the accuracy of forecasting electricity consumption and generation of electric energy using photovoltaic plant, data on energy storage system (current charge, maximum and minimum permissible charges), decision-making on optimization of power supply; organizational and technical mechanisms for the implementation of management functions – information and computing complex, energy dispatcher, chief energy engineer; the database of the electrical supply control system, which is used to prepare decisions; basic information flows that ensure the management of electricity supply – forecast values of meteorological data, current data on electric energy consumption, management actions on the regulation of photovoltaic plant and energy storage system, current data on power supply mode parameters; current data on power supply configuration; control actions on optimization of power supply regimes, management actions on the management of electricity quality indicators; control actions for changing the configuration of the power supply. The functional scheme of power supply control using photovoltaic plant and energy storage system is presented and the requirements for individual units are formulated. The synthesis of the food industry enterprise power supply control system is carried out using the method of ensuring compatibility through sequential integration. In order to ensure energy-efficient power supply of food industry enterprise and optimal use of photovoltaic plant and energy storage system, optimization of modes is carried out using dynamic programming methods. Conclusion. The development of control systems for power supply of food industry enterprise using photovoltaic plant and energy storage system based on system analysis and compatibility with the use of mode optimization using dynamic programming methods ensures high efficiency of power supply and rational modes of use of photovoltaic plant and energy storage system.
Keywords: electricity; control; supply; photoelectric; energy storage; кафедра електропостачання і енергоменеджменту; зберігання енергії; електрика; контроль; постачання